(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to determine whether the use of the Giving Question And Getting Answer learning model is effective in improving mathematics learning outcomes of MTs Islamiyah Medan students. This type of research is Classroom Action Research (CAR). The subjects of this research are the students of class VII-1 MTs Islamiyah Medan, amounting to 27 students. The object of this research is the Effectiveness of Using the Giving Question and Getting Answer Learning Model in Improving Student Mathematics Learning Outcomes at MTs Islamiyah Medan. Data collection techniques used were observation and tests. Observations are used to obtain the results of observations of students’ mathematical learning activities and tests are used to determine the increase in learning outcomes and the implementation of the learning process using the giving question and getting answer model. Data analysis techniques used are observation analysis, learning completeness analysis and classical completeness analysis. The results of observations of student activities with the Giving Question and Getting Answer model experienced a very good increase in cycle II. As for learning outcomes using the Giving Question and Getting Answer learning model is effective in improving mathematics learning outcomes students experience a significant increase in cycle II. This shows that the Completion Criteria is Classically ≥ 80%